2023
DOI: 10.1038/s41598-023-28622-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Chinese hamster ovary cells for co-overexpressing MYC and XBP1s increased cell proliferation and recombinant EPO production

Abstract: Improving the cellular capacity of Chinese hamster ovary (CHO) cells to produce large amounts of therapeutic proteins remains a major challenge for the biopharmaceutical industry. In previous studies, we observed strong correlations between the performance of CHO cells and expression of two transcription factors (TFs), MYC and XBP1s. Here, we have evaluated the effective of overexpression of these two TFs on CHO cell productivity. To address this goal, we generated an EPO-producing cell line (CHOEPO) using a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(74 reference statements)
2
6
0
Order By: Relevance
“…In contrast, the abundance of glutamine positively affected both transfectants, resulting in a similar growth rate of 0.9 day −1 , almost 24% higher than TAFE. While at low [Gln], h-XBP1s overexpression did not significantly influence μ, as all clones exhibited similar growth rates (∼0.7 day −1 ), aligning with the findings in CHO cells overexpressing XBP1s cultured with low glutamine concentration (2 mM) [ 27 ].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, the abundance of glutamine positively affected both transfectants, resulting in a similar growth rate of 0.9 day −1 , almost 24% higher than TAFE. While at low [Gln], h-XBP1s overexpression did not significantly influence μ, as all clones exhibited similar growth rates (∼0.7 day −1 ), aligning with the findings in CHO cells overexpressing XBP1s cultured with low glutamine concentration (2 mM) [ 27 ].…”
Section: Resultssupporting
confidence: 82%
“…In CHO cells, where the endogenous XBP1s factor is weakly expressed [ 31 ], overexpressing this transcription factor has proven to increase specific productivity by 5.4-fold for monoclonal antibodies [ 44 ], and by 4.5, 2.1, 5, and 2-fold for VEGF, SAMY, SEAP, and total protein, respectively [ 31 ]. Our research group has contributed to the evidence in CHO cells, showing only slight impacts of XBP1s overexpression over erythropoietin-specific productivity [ 27 ]. In B-cells, it has been shown that the mechanism behind these improvements involves the induction of genes facilitating protein translocation into the ER, protein folding, and trafficking in the secretory pathway [ 30 ], and expansion of the endoplasmic reticulum in CHO-K1-derived cell lines when XBP1s is overexpressed [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, intracellular and extracellular IgG levels were not significantly different from control cultures (Figure 7C,D), possibly since the cells were still in the early exponential phase (48 h post-inoculation) and protein production was insignificant at this time point. Thus, XBP1 splicing may be a more reli-able marker for productivity enhancement, since XBP1 splicing has been reported to correlate with antibody production, [105,106] likely through enhancement of molecular chaperone translation and protein folding and secretion. Note that molecular chaperone overexpression is indispensable for folding non-native, difficult-to-fold proteins.…”
Section: Rictor and Raptor Gene Knockdown Results In Reduced Upr Acti...mentioning
confidence: 99%
“…Moreover, promoter squelching might affect the overexpression of multiple target genes if their expression is driven by promoters using the same TRFEs. XBP-1s is a transcription activator involved in regulation of both protein secretion and the unfolded protein response and it is well studied in rProtein expression, 24,26,27 therefore in this study we sought to finely control the overexpression level of XBP-1s, using synthetic promoters of varying strengths and determine the impact on DTE mAb expression in CHO cells. The synthetic promoters contain TFREs for transcription factors that are abundant in CHO and are therefore not likely to be limited in their capacity to drive expression.…”
Section: Synthetic Promoter Technology Can Improve Expression Of a Dt...mentioning
confidence: 99%